ChemInform Abstract: CaTMg2 and CaTCd2 (T: Rh, Pd, Pt) with YPd2Si‐Type Structure. Issue 21 (2nd May 2013) - Johnscher, Michael; Kersting, Marcel; Matar, Samir F.; Poettgen, Rainer
Abstract The title compounds are prepared from mixtures of the elements by high‐frequency melting in Nb ampules or through reactions in muffle furnaces.